Child Discipline in Times of Conflict - Michael Malcolm; Vidya Diwakar; George S Naufal (Institute of Labor Economics (IZA), 2017)
Using a unique pairing of household survey data and geolocational conflict data, we investigate the relationship between local conflict intensity and the disciplinary methods employed by Iraqi households. We find that parents in high-conflict areas are more likely to use both moderate and severe corporal punishment, and are less likely to use constructive parenting techniques like redirection. While there is a general sense that war has profound long-term impacts on the psychological health of children, research on transmission mechanisms is very limited. These are among the first results that rigorously document an association between violent conflict and child maltreatment and, to our knowledge, the first that document changes in child discipline practices even across a mainstream parenting spectrum. Given the persistence of early childhood outcomes into adulthood, these results are potentially an important piece of assessing and mitigating the long-term costs of war on the civilian population.
Keywords: D10; F51; J13; N45; 330; Iraq war; child discipline; mental health; Middle East; household interactions